Peran Otoritas Jasa Keuangan dalam Pemberantasan Tindak Pidana Penipuan Yang Memanfaatkan Rekening Bank Sebagai Rekening Penampungan - Selamat Widodo; Ika Ariani Kartini (Kosmik Hukum, 2022)
The rise of fraud with various modes has worried the public a lot, especially fraud by electronic means. The modus operandi of the perpetrators of the crime varies, ranging from online buying and selling, lottery winners, claiming to be officers, to news reports of relatives who have had an accident and need money to pay for the treatment process. After the victim is deceived, the perpetrator will ask the victim to transfer a certain amount of money to a certain bank account that has been determined by the perpetrator. After the victim transfers a certain amount of money, the perpetrator immediately transfers or withdraws all the money in his account. The purpose of the establishment of OJK is that all activities in the financial services sector can be carried out in an orderly, fair, transparent and accountable manner. Then be able to realize a financial system that grows in a sustainable and stable manner and is able to protect the interests of consumers and the public. In order for the public to get protection from the abuse of crime from parties who are not responsible for bank accounts used as a repository for the proceeds of crime, strict supervision and regulation is necessary. This is one of the duties and roles of OJK in providing protection to the public. One of the powers possessed by OJK is banking supervision. In the existing provisions, banks are required to apply the principle of know your customer or CDD (coctumer due dilligent), namely the principle of knowing your customer. So that in the event that the perpetrator of a crime uses his account as a means of crime, law enforcement officers can immediately make arrests and legal proceedings, because the customer has been known and recognized by the bank.Keywords: Financial Services Authority, Know Your Customer/Customer Due Dilligent Principle, Bank account.